2015
DOI: 10.1038/mp.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

The C9orf72 repeat size correlates with onset age of disease, DNA methylation and transcriptional downregulation of the promoter

Abstract: Pathological expansion of a G4C2 repeat, located in the 5' regulatory region of C9orf72, is the most common genetic cause of frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). C9orf72 patients have highly variable onset ages suggesting the presence of modifying factors and/or anticipation. We studied 72 Belgian index patients with FTLD, FTLD–ALS or ALS and 61 relatives with a C9orf72 repeat expansion. We assessed the effect of G4C2 expansion size on onset age, the role of anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
248
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(262 citation statements)
references
References 79 publications
(167 reference statements)
10
248
1
Order By: Relevance
“…1). Because the expanded repeat is not present in the reference, these paired IRRs may not align to the C9orf72 repeat locus and could either not align at all or misalign to a different locus in the genome (Church et al 2015;Gijselinck et al 2016). To identify unaligned or misaligned IRRs, we tested every (MAPQ = 0) read in all 182 expanded ALS samples of the first cohort identified by the first round of RP-PCR as having the C9orf72 repeat expansion.…”
Section: Off-target Irrsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Because the expanded repeat is not present in the reference, these paired IRRs may not align to the C9orf72 repeat locus and could either not align at all or misalign to a different locus in the genome (Church et al 2015;Gijselinck et al 2016). To identify unaligned or misaligned IRRs, we tested every (MAPQ = 0) read in all 182 expanded ALS samples of the first cohort identified by the first round of RP-PCR as having the C9orf72 repeat expansion.…”
Section: Off-target Irrsmentioning
confidence: 99%
“…Because high-throughput WGS technologies are currently limited to ∼150 base pair (bp) read lengths, variantcalling methods that rely on reads aligned to the reference are subsequently limited to repeat lengths less than 150 bases (Narzisi and Schatz 2015). Many pathogenic repeat expansions have repeats spanning hundreds to thousands of base pairs (Dürr et al 1996;Gatchel and Zoghbi 2005;Kronquist et al 2008;Gijselinck et al 2016), so it has been assumed that short-read sequencing technologies may not be able to identify pathogenic repeat expansions (Loomis et al 2013;Ashley 2016).…”
mentioning
confidence: 99%
“…Alongside holistic methylation studies, others have focused on the methylation status of the C9orf72 gene promoter, shown to be hypermethylated in expansion carrier ALS and FTD patients [19-22]. Such aberrant methylation has been suggested to be a disease modifier acting through a loss-of-function [23] rather than a toxic gain-of-function mechanism [12, 24]. …”
Section: Introductionmentioning
confidence: 99%
“…This discovery has opened the path for progress in the knowledge and treatment of these devastating diseases. C9ORF72 HRE-linked pathogenesis has been suggested to be elicited by means of loss-offunction and toxic gain-of-function mechanisms that comprise the following: (1) transcribed sense GGGGCCexp or antisense (CCCCGGexp) RNAs that sequester proteins, therefore interfering with their physiological function [8]; (2) sense or antisense expanded RNAs that are translated via repeatassociated non-AUG initiated (RAN) translation to generate toxic dipeptide repeat proteins (DPRs) [10][11][12][13]; or (3) haploinsufficiency that originates from diminished transcription of the C9ORF72 exonic sequence [14,15] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%